Uso do SIG no suporte ao planejamento turístico do município de Pinhal Grande - RS - Rossato, Alexandre (2004)
The tourism is seen now as a successful, and highly profitable economical section, as well as one of the sections that can produce a large number of jobs, then its great importance to a country, and even to a town. However, it is necessary to plan and to invest with its process of development, which passes mainly by the knowledge of the tourist potentialities. In that sense, it is located Pinhal Grande -RS, subject of the present dissertation, which belongs to the area of Fourth Cologne of Italian Immigration, where the tourist activity is integrated and tried to be developed. The general purpose of this work was to supply data and information for the planning and development of the tourist activity of Pinhal Grande. Specifically the tourist potentialities of the town were mapped and diagnosed, a Tourist Map was elaborated, by using the SIG, spatially locating the tourist points, equipment and support services to the activity, and a database, related to the goods and tourist services, containing necessary information to give support its planning was modeled. To reach the proposed goals, the methodology presented by Magalhães (2002), which guides the formulation and application of the investigative offer questionnaire and tourist demand and of public opinion. The results evidenced that from the association of information obtained through the offer, public opinion and tourist demand it was verified that the town presents a tourist vocation, with an excellent offer of historical-cultural attractions and significant natural attractions. From this association, some negative points were also observed such as the accessibility to the town and to the attractions, the amount and the quality of equipment, and support services to the tourist. In this research, two cartographic documents were made - Image Charge and Tourist Map of Pinhal Grande and, modeling of a database for contributing to the stimulation of the tourist demand, as well as, to aid the managers in the planning and tourism administration. Before the presented information, it is recommended the managers to maintain it updated, and SIG allows it to be done in larger speed and reliability. It is good to remind that tourism can only grow successfully, in an organized and articulated way.